2019
DOI: 10.15252/embj.2018100809
|View full text |Cite
|
Sign up to set email alerts
|

Live‐cell imaging reveals the interplay between transcription factors, nucleosomes, and bursting

Abstract: Transcription factors show rapid and reversible binding to chromatin in living cells, and transcription occurs in sporadic bursts, but how these phenomena are related is unknown. Using a combination of in vitro and in vivo single‐molecule imaging approaches, we directly correlated binding of the Gal4 transcription factor with the transcriptional bursting kinetics of the Gal4 target genes GAL3 and GAL10 in living yeast cells. We find that Gal4 dwell time sets the transcriptional burst size. Gal4 dwell time depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
233
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(251 citation statements)
references
References 64 publications
(94 reference statements)
17
233
1
Order By: Relevance
“…In contrast, live imaging of the nascent mRNA could put constraints on T E [1]. In that case, the filtering time scale is the elongation time, typically on the order of a few minutes, while the reported transcriptional response times—and thus estimates of T E —would range from minutes to 1 − 2 hours [9, 26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, live imaging of the nascent mRNA could put constraints on T E [1]. In that case, the filtering time scale is the elongation time, typically on the order of a few minutes, while the reported transcriptional response times—and thus estimates of T E —would range from minutes to 1 − 2 hours [9, 26].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, short TF residence times (ii) and the importance of TF arrival ordering (iii) contradict the conceptual picture where stable enhanceosomes are assembled in equilibrium [4]. Kinetic schemes may be required to match the reported characteristics of bursty gene expression (vi) [26], or realize high cooperativity (vii) [27]. Thermodynamic models undisputedly have statistical power to predict expression from regulatory sequence even in eukaryotes [28], yet this does not resolve their biophysical inconsistencies or rule out non-equilibrium models.…”
mentioning
confidence: 99%
“…First, in the last decade methods to quantify the ability of a regulated gene to acquire information about the concentration of a TF have become standardized (10,44). Also, the effect of residence time on noise can be quantified with techniques that simultaneously quantify TF-DNA binding events and the production of mRNA molecules, which are being developed (16). It is especially difficult to obtain multiple alleles of a TF with different residence times without also altering the TF's affinity to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The residence time is equal to the inverse of the dissociation rate kd between a TF and DNA. Theoretical and experimental work has shown that the dissociation rate can affect gene expression, affect the size of gene expression bursts (16)(17)(18)(19), and modulate gene expression noise (20)(21)(22)(23). However, it is difficult to discern whether the dissociation rate affects gene expression by altering the residence time or the affinity between a TF and DNA, because both depend on the dissociation constant kd (affinity is given by the ratio Keq=kd/ka [M], where ka is association rate between a TF and DNA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation